EFEK KECANDUAN MEDIA TIK TOK TERHADAP PERILAKU SOSIAL REMAJA - lisa Sis Mona; Irman Irman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Tiktok social media is one of the fastest growing social media platforms in the world, excessive use of social media by teenagers will have a negative impact on academic performance at school, teenagers become lazy and irresponsible with their duties, resulting in teenagers not having time to study. This research uses qualitative research with a descriptive approach. A person's social behavior can be influenced during the learning process through motivation and influence from the surrounding environment. Peers can have an influence on the use of TikTok, from those who don't initially use TikTok to those who end up using TikTok. Teenagers with social media addiction are more likely to experience various negative problems including problems in social behavior.